E-019 TCAR. (23rd July 2022) - Bajaj, A; Monje, S; Ayala, C; Poggi, J; Shaaya, E; Feler, J; Moldovan, K; Doberstein, C; McTaggart, R; Torabi, R
Abstract : Introduction: Transcarotid artery revascularization (TCAR) has emerged as a safe alternative to carotid endarterectomy (CEA) and peripheral carotid stenting for treating patients with carotid artery stenosis. The safety and efficacy of TCAR in patients with carotid stenosis has been established by several studies, beginning with the multicenter ROADSTER trial. However, only 36 of the 141 patients in the ROADSTER study population (26%) were symptomatic, and limited data exist concerning the utility of TCAR for patients with symptomatic carotid stenosis. The objective of this study is to validate the safety and efficacy of TCAR in a single-center cohort of patients with symptomatic carotid artery stenosis. Methods: We identified all patients with symptomatic carotid stenosis who underwent TCAR at Rhode Island Hospital between 11/01/2020 and 11/30/2021. Relevant demographic, comorbidity, and perioperative data were extracted through retrospective chart review. We also evaluated patients using pertinent physiologic and anatomical high-risk criteria as described in the ROADSTER trial. Risk factors were aggregated to form a composite risk total for every patient. The primary outcome of this study was the 30-day adverse outcome rate of stroke, MI, and/or death. Periprocedural stroke was identified by clinical symptoms and radiographic findings. Secondary endpoints included acute device and procedural success, 30-day mortality, 30-day stroke rate, and postoperative complications. All means are reported with standard deviations, and analysis of variance (ANOVA) was used to assess the statistical significance of differences between patients in different composite risk tiers. Results: We analyzed the first 47 patients with >50% symptomatic carotid stenosis who underwent TCAR at our institution. The average age was 71.4 years old (standard deviation = 10.5), and the majority of patients were male (72.3%). High cervical carotid stenosis (34.0%), hostile neck anatomy (12.8%), and restenosis after prior CEA (8.5%) were the most frequent anatomic high-risk criteria which patients in the study fulfilled. The most common physiologic high-risk factors among the study cohort were age >75 years (46.8%), > 2 vessel coronary artery disease with history of angina (12.8%), severe COPD (8.5%), and class III/IV congestive heart failure (8.5%). The all-cause adverse outcome rate of stroke, death, and MI was 4.3%. Among these patients, one died within 30 days of the procedure from symptomatic intracranial hemorrhage that developed 3 days post-procedure, and the other died of gastroenteritis unrelated to the procedure. No patients experienced a stroke within 30 days of the procedure. Postoperatively, one patient developed a neck hematoma requiring surgical evacuation, and another patient had an iatrogenic access site carotid dissection seen on follow-up imaging without clinical sequelae. Stratifying the study cohort across composite high-risk criteria, one-way ANOVA demonstrated no significant difference in adverse outcome rate between groups of patients who met 0, 1, 2 or ≥ 3 high-risk criteria (p = 0.76). Conclusions: Our analysis of a single-center cohort demonstrates that TCAR is a safe and effective treatment for symptomatic carotid stenosis, with a low perioperative stroke risk. The present study's findings concur with the combined adverse outcome rate of 3.5% reported in the ROADSTER trial. Disclosures: A. Bajaj: None. S. Monje: None. C. Ayala: None. J. Poggi: None. E. Shaaya: None. J. Feler: None. K. Moldovan: None. C. Doberstein: None. R. McTaggart: None. R. Torabi: None.